2017
DOI: 10.1177/1060028017737095
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants in Cardioversion: A Review of Current Evidence

Abstract: DOACs may be an attractive alternative to warfarin because of fast onset of action, potentially reducing delay to cardioversion. More robust studies are needed in patients with renal dysfunction and patients undergoing pharmacological cardioversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…RCTs and meta-analysis have demonstrated the safety and efficacy of DOAC in patients undergoing ECV [7][8][9][26][27][28]. Our results are in line with the outcome of the 3 RCTs focusing on pericardioversion DOAC (Appendix C).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 85%
“…RCTs and meta-analysis have demonstrated the safety and efficacy of DOAC in patients undergoing ECV [7][8][9][26][27][28]. Our results are in line with the outcome of the 3 RCTs focusing on pericardioversion DOAC (Appendix C).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 85%
“…The trial showed a significant reduction with apixaban in strokes (0% vs. 0.8%) and in major bleeding (0.4% vs. 0.8%) at 30 days compared to warfarin. The favorable clinical profile of NOACs in patients undergoing CV has also been confirmed in a recent metanalysis [59,60] and in real-world studies [61,62,63,64,65,66].…”
Section: Prevention and Treatment Of Left Atrial Appendage Thrombosismentioning
confidence: 65%
“…Finally, DOACs demonstrated good predictable onset of anticoagulation (since 1 to maximum 4 h) compared with 48 to 72 h for warfarin and up to 5 to 7 days to reach steady state [36,37]. In a very interesting random-effects meta-analysis performed by Brunetti et al [38], a total of 8564 patients undergoing both electrical and pharmacologic cardioversions for NVAF were included observing, one more time, the effectiveness and safety of DOACs in patients undergoing NVAF.…”
Section: Discussionmentioning
confidence: 99%